Effect of pH on the growth of zinc oxide nanorods using Citrus aurantifolia extracts - Rafaie, H.A.; Samat, N.A.; Nor, R.M. (Elsevier, 2014)
The effect of pH during sal gel synthesis of ZnO nanorods using Citrus aurantifolia juice extracts has been investigated. Zinc nitrate solutions and C aurantifolia fruit extracts mixtures were heated at 90 degrees C at pH of 5, 7 and 9. Solid reaction products were annealed in air at 300 degrees C yielding nanorods with diameters of about 100 nm for all samples. XRD analysis showed pure hexagonal wurtzite ZnO structure. Room temperature visible photoluminescence spectroscopy revealed emissions which were attributed to the common defects states associated with ZnO. Nanorods growth in acidic solution was found to be inhibited compared to nanorods from neutral and alkaline solutions. This was due to preferential erosion of ZnO (0001) face in acidic solution and the enhanced growth in neutral and alkaline solutions which favored the formation of Zn(OH)(2) which is an intermediate molecule in the reaction to form ZnO. (C) 2014 Elsevier B.V. All rights reserved.